Implementation fidelity of a community-based Aedes aegypti breeding site elimination program for dengue control in southeastern Mexico - Miguel Mazariego-Longoria; Carlos Rojas-Arbeláez; Héctor Vélez-Santamaría; Abel Jiménez-Alejo; Ariane Dor; Guillermo Rúa-Uribe (PLoS ONE, 2026)
Introduction Dengue is a globally significant arboviral disease in tropical regions such as southeastern Mexico. The “Healthy Environments and Communities” (E&CS) program, led by the Health Secretariat, promotes community practices to eliminate Aedes aegypti breeding sites. However, factors influencing its implementation and fidelity remain unclear. Objective To determine the factors affecting fidelity in implementing the E&CS program targeting breeding site elimination in Río Florido, Tapachula. Methods An observational mixed-methods study was conducted. The quantitative component evaluated fidelity among health personnel using a CFIF-based instrument, measuring Content Details, Frequency, Duration, and Coverage. Independent-samples t-tests compared mean fidelity scores between subgroups (DSVII and CSLL). The qualitative component included semi-structured interviews with health personnel and community members, coded using a priori CFIR categories and emergent themes to identify barriers and facilitators. Frequencies of barriers and facilitators among health personnel subgroups were compared using Fisher’s exact test, and chi-square tests assessed differences in distribution. Results Overall mean fidelity was 91.2% (95% CI: 88.5–93.4%). By construct, Content Details reached 92.4%, Frequency 89.8%, Duration 90.5%, and Coverage 91.3%. Among health personnel (n = 23; 142 responses), Fisher’s exact test showed no significant differences (p > 0.05). After combining responses, the distribution did not differ from chance (χ² = 9.73, df = 6, p = 0.136). In the Río Florido community, significant differences were observed (χ² = 83.16, df = 11, p < 0.001). Main barriers included “insufficient attention from the health center” and perceiving the Health Secretariat as responsible for dengue. Key facilitators were recognition of E&CS, respectful relationships with health personnel, and belief in program success. Conclusion High fidelity of the E&CS program (>90%) in Río Florido was accompanied by a differentiated pattern of barriers and facilitators, balanced among health personnel but uneven in the community. Addressing these factors through an implementation research (IR) approach could strengthen the sustainability and effectiveness of dengue control strategies.